The Golo Koe Festival: Implementation of Holistic Tourism and Religious Moderation in Labuan Bajo - Berybe, Gregorius; Rudianto, Roseven (MSJ : Majority Science Journal, 2023)
The Golo Koe Festival in Labuan Bajo City has become an integral part of efforts to expand the introduction of Labuan Bajo as an inclusive tourism destination. The festival not only highlights the beauty of marine nature, but also showcases the rich cultural heritage and religious diversity that emerges in people's lives. This study aims to explore the implementation of the concept of religious moderation in the Golo Koe Festival as a form of holistic tourism. Through a descriptive qualitative approach, this study highlights national commitment, tolerance, rejection of violence, and accommodation to local culture as indicators of religious moderation in the Golo Koe Festival. Primary data collection is carried out through observation and structured interviews with respondents who are parties involved as committees, visitors, tenants and talents. Determination of samples using non-random sampling with purposive sampling techniques where researchers can directly select parties who at the time of the Golo Koe Festival became respondents, while secondary data were obtained from various related literature. The collected data is analyzed through stages: reducing data, presenting data and verifying data to draw conclusions. Data validation is done by source triangulation. The results showed that the festival plays an important role in raising awareness of tolerance, interfaith involvement, and promotion of local culture. Golo Koe Festival is not only a tourism event, but also a vehicle to promote religious moderation and strengthen diversity as an asset in promoting the values of religious moderation in strengthening Labuan Bajo's positive image as a friendly and inclusive tourist destination.